Another way of learning double entry in accounting: the mnemonic approach / Maisarah Abd Rahim - Abd Rahim, Maisarah (Faculty of Accountancy, UiTM Kedah, 2018)
Students typically associate accounting subjects with negative perceptions. When the word “accounting” is mentioned, students think it is a scary subject. As a beginner, learning accounting is considered very tough. Such a negative presumption towards learning accounting subjects is widespread. As for an educator, it is very challenging nowadays to deliver especially accounting knowledge to the current generation who is widely exposed to social media; Facebook, Twitter, Instagram, WhatsApp, YouTube, etc. Today‟s generation‟s learning styles are mostly dependent on digital technology and they do not learn without the internet. Moreover, preparing towards Education 4.0 is more challenging as we acknowledge that innovation is a key driver towards Education 4.0